Knockout mice for dyslexia susceptibility gene homologs KIAA0319 and KIAA0319L have unaffected neuronal migration but display abnormal auditory processing - Guidi, L; Mattley, J; Martinez-Garay, I; Monaco, A; Linden, J; Velayos Baeza, A; Molnar, Z (Oxford University Press, 2017)
Developmental dyslexia is a neurodevelopmental disorder that affects reading ability caused by genetic and non-genetic factors. Amongst the susceptibility genes identified to date, KIAA0319 is a prime candidate. RNA-interference experiments in rats suggested its involvement in cortical migration but we could not confirm these findings in Kiaa0319- mutant mice (Martinez-Garay et al. 2017). Given its homologous gene Kiaa0319L (AU040320) has also been proposed to play a role in neuronal migration, we interrogated whether absence of AU040320 alone or together with KIAA0319 affects migration in the developing brain. Analyses of AU040320 and double Kiaa0319;AU040320 knockouts (dKO) revealed no evidence for impaired cortical lamination, neuronal migration, neurogenesis or other anatomical abnormalities. However, dKO mice displayed an auditory deficit in a behavioural gap-in-noise detection task. In addition, recordings of clickevoked auditory brainstem responses revealed suprathreshold deficits in wave III amplitude in AU040320-KO mice, and more general deficits in dKOs. These findings suggest that absence of AU040320 disrupts firing and/or synchrony of activity in the auditory brainstem, while loss of both proteins might affect both peripheral and central auditory function. Overall, these results stand against the proposed role of KIAA0319 and AU040320 in neuronal migration and outline their relationship with deficits in the auditory system.